Produção inicial e qualidade de frutos de cinquenta e sete copas de laranjeira doce sobre quatro porta-enxertos no extremo sul da Bahia - Buffon, Stanley Bravo (2020)
Prior knowledge of scion/rootstock combinations is essential for establishing appropriate citrus orchard management strategies. Focusing on sweet orange trees, in the Municipality of Ibirapuã, Extreme South of Bahia, the objective was to identify among 228 scion/rootstock combinations those that present the highest productivity and fruit quality. The harvests were carried out from April to August 2019, when the plants reached 4.5 years old. The number, total mass and transverse diameter of the fruits, productive efficiency, pulp yield, soluble solids content, titratable acidity and ratio were evaluated. There was a statistical difference for all characteristics related to production and fruit quality regarding the factors studied and their combinations. Among the ‘Pera’ orange clones studied, the ‘Pera CNPMF A-15’/citrandarin ‘San Diego’ and ‘Pera CNPMF D-3’/citrandarin ‘Riverside’ combinations stood out the most. The orange 'Sincorá', in combination with the citrandarins 'San Diego' and 'Indio', has the potential to be recommended to producers who wish to anticipate their harvests, as well as the orange 'Natal Ipeal' in combination with the citrandarin 'Indio', in the sense of postponing them. This ‘Natal’ clone showed a substantial reduction in tree canopy volume, associated with high productive efficiency, which qualifies it for use under high planting densities. In this regard, studies on planting density are recommended, especially for the combinations that presented lower tree canopy volumes and high production efficiency